2006
DOI: 10.2116/analsci.22.205
|View full text |Cite
|
Sign up to set email alerts
|

Microcantilevers Modified by Horseradish Peroxidase Intercalated Nano-Assembly for Hydrogen Peroxide Detection

Abstract: Detection of hydrogen peroxide is of industry interest and of biological importance. Here we report a new approach to hydrogen peroxide measurement using multilayer modified microcantilevers. Through a layer-by-layer nanoassembly technique, horseradish peroxidase was intercalated into a nanoscale multilayer assembly on one surface of microcantilevers.These enzyme-functionalized microcantilevers deflected in response to hydrogen peroxide concentrations in the nanomolar level. The magnitudes of bending were prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Interestingly, the results showed that the conformational change of the GOx enzyme upon complexation with glucose was the main origin of cantilever deflection [47]. Another recent publication further proved this concept [48].…”
Section: Enzyme-based MCL Biosensorsmentioning
confidence: 87%
“…Interestingly, the results showed that the conformational change of the GOx enzyme upon complexation with glucose was the main origin of cantilever deflection [47]. Another recent publication further proved this concept [48].…”
Section: Enzyme-based MCL Biosensorsmentioning
confidence: 87%
“…Similar phenomena have been observed on other enzymes, such as organophosphorus hydrolase (OPH) 41 and horseradish peroxidase (HRP). 42 In both cases, calculations showed that the conformational changes of the enzymes contribute greatly to cantilever bending.…”
Section: Surface Stress Change Resulted From Conformational Change Of...mentioning
confidence: 99%
“…Detection of hydrogen peroxide is both of industry interests and of biological importance. Yan et al developed 44,39 MCL sensors for H 2 O 2 detection. The MCLs were modified by horseradish peroxidase (HRP) through a layer-by-layer nanoassembly technique.…”
Section: Hydrogen Peroxide (H 2 O 2 )mentioning
confidence: 99%